Quantitative phase imaging of cancerous cell by inverted polarization digital holographic microscope - Rathor M.; Chaubey S.K.; Tamang R.; Koch B.; Singh R.K. (My University, 2025)
We present a digital holographic microscope in the inverted geometry to extract the real-time quantitative polarization information of cancerous cells. Our technique is non-invasive and uses a single-shot intensity measurement for complete wavefront measurement. © Optica Publishing Group 2024, © 2024 The Author(s)